PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN MEDIA SOSIAL TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Eka Astra Susilawaty (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2022)
This study aims to determine the impact of entrepreneurship education and social media on student entrepreneurship interest. Students who graduate from college faced difficult condition on getting a job due to the unavailability of job opportunities. The interest in entrepreneurship through entrepreneurship education in college and the development of information technology through the existence of social media and the internet provide opportunities to create an independent generation oriented to the construction of new jobs in order to suppress the increase in unemployment. This research was conducted with a quantitative approach. The sample in this study were 63 respondents from sixth semester students, Diploma III Accounting study program and eighth semester students, Diploma IV Managerial Accounting study program, Accounting Department, State Polytechnic of Ujung Pandang. The primary data obtained from the distribution of questionnaires through google form. The results of this study indicate that partially entrepreneurship education has a significant influence on student entrepreneurship interest, while social media has no effect on student entrepreneurial interest. However, the influence of the variables of entrepreneurship education and social media on the interest in entrepreneurship simultaneously has an effect of 51.5%.